Pengaruh Motivasi, Komunikasi, dan Stres Kerja terhadap Kepuasan Kerja Karyawan PT. Karunia Global Lestari - Natalius Tarigan; Charles Ganda Maruli Siagian; Habib Hakim; Dahnil Anjar Simanjuntak (MAMEN: Jurnal Manajemen, 2025)
This research was conducted at PT. Karunia Global Lestari. The study aims to determine the influence of motivation, communication, and work stress on employee job satisfaction at PT. Karunia Global Lestari. The population of this study consisted of 80 employees of PT. Karunia Global Lestari, located on Jalan Moh. Yakub Lubis, Bandar Klippa, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The sample used in this study comprised 80 respondents, selected using a saturated sampling technique. Data collection was carried out using a questionnaire. The data analysis technique employed was multiple linear regression analysis. The results of the study indicate that, partially, motivation has a positive and significant effect on employee job satisfaction, communication has a positive and significant effect on employee job satisfaction, and work stress has a negative and significant effect on employee job satisfaction at PT. Karunia Global Lestari. Simultaneously, motivation, communication, and work stress have a significant effect on employee job satisfaction at PT. Karunia Global Lestari. These findings imply that companies need to improve motivation and effective communication, as well as minimize work stress to increase employee job satisfaction.